Protective Association Between Calcium Channel Blocker Use and Breast Cancer Recurrence in Postsurgical Women: A Population‐Based Case‐Control Study in Taiwan - Shih, Jui‐Hu; Kao, Li‐Ting; Chung, Chi‐Hsiang; Liao, Guo‐Shiou; Fann, Li‐Yun; Chien, Wu‐Chien; Li, I‐Hsun (Journal of clinical pharmacology)
Neoadjuvant chemotherapy induces metastasis of residual breast cancers through activation of tumor‐associated macrophages. Previous studies have indicated that calcium channel blockers (CCBs) exert anti‐inflammatory and antimigratory effects on macrophages via attenuating Ca2+ entry into macrophages. However, no existing empirical research has addressed the relationship between previous CCB use and breast cancer recurrence. In this study, 4840 Taiwanese women aged ≥20 years with breast cancer who underwent breast surgery from January 1, 2007, to December 31, 2015, were enrolled. The date of cancer recurrence was defined as the index date. Logistic regression was performed to evaluate the relationship between previous CCB exposure and cancer recurrence among female patients who underwent surgery for breast cancer. After adjusting for demographic characteristics, comorbidities, and tumor‐node‐metastasis stage, the adjusted odds ratio (OR) for CCB exposure within 5 years before the index date in women with recurrence compared with nonrecurrent controls was 0.73 (95% confidence interval [CI], 0.53‐0.97). Further analysis revealed that the adjusted OR for CCB exposure between the surgery and index dates in women with recurrence relative to nonrecurrent controls was 0.72 (95%CI, 0.66‐0.95). In particular, prior CCB use was significantly associated with a lower risk (34%) of breast cancer recurrence among women 20 to 54 years old (OR, 0.66; 95%CI, 0.47‐0.83). This study uncovered a protective association between previous CCB use and breast cancer recurrence.